2011
DOI: 10.1021/jf104177x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Protein Isolates Extracted from Stabilized Rice Bran by Microwave, Dry Heat, and Parboiling

Abstract: Protein isolates extracted from differently stabilized rice bran were analyzed to work out the food use potential. Bulk density remained higher for isolates obtained from heat stabilized bran, the treatments were found to have positive impact on the oil absorption properties, while the water absorption was slightly impaired owing to some possible configurational changes. Surface hydrophobicity and emulsion properties were improved with bran stabilization. Isolates exhibited better foaming properties owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 29 publications
2
61
2
1
Order By: Relevance
“…Khan et al . () also found that heat stabilisation treatment could reduce the foaming property of rice bran protein. Moreover, the application of protein sample would be limited in the food industry due to the destruction of foaming property.…”
Section: Resultsmentioning
confidence: 97%
“…Khan et al . () also found that heat stabilisation treatment could reduce the foaming property of rice bran protein. Moreover, the application of protein sample would be limited in the food industry due to the destruction of foaming property.…”
Section: Resultsmentioning
confidence: 97%
“…Also, ES result obtained in this study was higher than the values (40.50–51.20%) reported by Khan et al . () for rice protein isolated from stabilised rice bran by microwave, dry heat and parboiling.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, the intake of rice bran (RB) by humans was short due to the development of the quick rancidity, but these days stabilization methods and extraction of oil have been introduced [1,2]. Interest in RB is increasing because a number of studies suggest that the consumption of rice bran produces potential health benefits.…”
Section: Introductionmentioning
confidence: 99%